Disrobing behaviour in a forensic inpatient, a case report - Dupré, Juliette (The journal of forensic psychiatry & psychology, 2023)
Disrobing is a behaviour with serious implications for sexual safety. It is a challenge to manage in the inpatient environment and a barrier to discharge to the community. This paper presents an overview of the literature on disrobing – distinct from exhibitionistic disorder – and primarily described in the developmental disabilities’ literature, and with respect to affective psychoses and epileptic post-ictal states. A case of disrobing in a forensic inpatient is outlined, which does not easily fit within the previously described explanatory or diagnostic paradigms for this behaviour. Behavioural and psychological analyses are reported, leading to a formulation of disrobing in this case as a complexly derived behaviour in a patient with chronic psychotic illness and a history of childhood sexual abuse. The importance of transdiagnostic thinking in patients with such complex histories is reviewed with attention to the intersection of deficits in distress tolerance from chronic psychotic illness and childhood sexual trauma. This case highlights the need for more research into trauma-informed interventions suitable for the serious mental illness (SMI) population.